Parvovirus infection and anaemia in a patient with AIDS: case report. Issue 2 (April 1990) - Mitchell, S A; Welch, J M; Weston-Smith, S; Nicholson, F; Bradbeer, C S
Abstract : Opportunistic infections such as Pneumocystis carinii pneumonia are well-recognised in patients with the acquired immune deficiency syndrome (AIDS). Anaemia due to a variety of causes also occurs in AIDS. Persistent infection with parvovirus (B19) causing severe anaemia has been reported in patients with leukaemia and congenital immunodeficiency. A case is now reported of parvovirus infection and anaemia, in an adult with AIDS, which responded dramatically to immunoglobulin therapy.